Estudio de factibilidad para la implementación de un centro de servicios (serviteca) para reparaciones menores mecánicas, suministro de repuestos y accesorios para automóviles en Bogotá D.C. (2019)
The purpose of this feasibility study was to create a service provision company focused on the automotive maintenance sector in the city of Bogotá. The project was developed based on the implementation of an establishment that offers a comprehensive and quality service, in which users feel confident in the service provided. With the market study a great demand was identified that tries to find an establishment that meets their needs in a logical way. Likewise, the services with greater demand within the sector were identified and, in this way, to be able to cover the different needs of the users. In the same way, it is intended to add different proposals for added value, which differentiate from competitors, in order to create a great impact on the environment.